2016
DOI: 10.1007/s12613-016-1365-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shielding gas on the mechanical and metallurgical properties of DP-GMA-welded 5083-H321 aluminum alloy

Abstract: In the present research, 6-mm-thick 5083-H321 aluminum alloy was joined by the double-pulsed gas metal arc welding (DP-GMAW) process. The objective was to investigate the influence of the shielding gas composition on the microstructure and properties of GMA welds. A macrostructural study indicated that the addition of nitrogen and oxygen to the argon shielding gas resulted in better weld penetration. Furthermore, the tensile strength and bending strength of the welds were improved when oxygen and nitrogen (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As a result, fewer pores were created in samples that received medium and moderate heat input. In addition, the increase in the fluidity of the molten pool increases the likelihood that trapped gases will escape and give birth to improved mechanical characteristics because of the low porosity [17,18].…”
Section: Validation Of Optimized Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, fewer pores were created in samples that received medium and moderate heat input. In addition, the increase in the fluidity of the molten pool increases the likelihood that trapped gases will escape and give birth to improved mechanical characteristics because of the low porosity [17,18].…”
Section: Validation Of Optimized Resultsmentioning
confidence: 99%
“…The presence of the dimples is a crucial aspect of a ductile fracture because the size of the dimples reveals the material's ductility. High-strength materials are indicated by fine dimples, whereas low-strength materials are indicated by large dimples [17]. Since figure 7(a) has many small dimples, it shows that the AA5083 base metal is strong and ductile.…”
Section: Fractographic Analysismentioning
confidence: 99%
“…[8] Among the various fusion welding processes reported to date, tungsten inert gas (TIG) welding is one of the most widely used methods due to its high production efficiency, low cost, wide applicability, and high flexibility. [9][10][11] To date, the microstructures and properties of welded aluminum alloy joints have been investigated by a number of research groups. [12][13][14] For example, Xu et al [15] studied the mechanical properties and microstructures of the TIG joints of the Al-Mg-Mn-Sc-Zr alloy, and they found that the lowest hardness was located in the weakened heat-affected zone (HAZ), and that tensile cracking both started and remained in the HAZ, ultimately leading to a reduction in the tensile properties.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal simulation technique can test materials under dynamic thermal-mechanical loading, replicate real manufacturing process in the laboratory, and has been widely utilized to study the hot-formability and microstructure of aluminum alloys [4,5]. It is documented that the hot deformation behavior of aluminum alloys is affected by alloying elements [6][7][8], as the addition of solute elements may increase the dislocation density and hinder the dislocation motion. Thus, the mobility of grain boundaries is reduced [9,10].…”
Section: Introductionmentioning
confidence: 99%